Identificación de Patrones Emocionales Básicos en Publicidad Audiovisual Utilizando Modelos Vectoriales por Adaptación - Arango, Sebastián; Maturana, Miryam; Ruiz, Lorena (KnE Engineering, 2018)
At present, the analysis of the results of advertising and marketing studies is done qualitatively in terms of the experience of a marketing analyst, thus generating little certainty and uncertainty of the effectiveness of the feelings and the message emitted. Brands are connected with the idea that the sender wants to transmit. For this, the marketing has studied the behavior of the consumer when exposed to different advertising stimuli, in order to understand the behavior at the time of the stimulus and to achieve alignment of the message to be transmitted with what is actually perceived. In this paper we propose a vector model based on computational intelligence and Neuromarketing studies that allows the identification of four basic emotions: joy, fear, anger and sadness from the bioelectric brain activity recorded by a person exposed to a certain audiovisual advertising. The results of the model allowed the identification of emotions in audiovisual advertising, which constitutes a tool that allows companies to create audiovisual advertising that guarantees greater commitment and effectiveness of the advertising segments with which it wants to impact the market Keywords: Neuromarketing, audiovisual advertising, basic emotions, neural networks, Emotiv-EPOC®, vector support machines